A/r/tografia de um corpo-experiência: arte contemporânea, feminismos e produção de subjetividade - Stubs, Roberta [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Using my experience as a psychologist and visual artist, with this research I come up with the proposal to create intercessors between art and psychology in order to think and produce forms of subjectivity affected to becoming and multiplicities. Believing in the ethic, aesthetic and political relevancy in investing in the production of plural and post-identitarian subjectivities, this research explores art as a vector potentially capable of enriching and singularizing our experience fields. The differences are been positivated as alterity, and this enrichment assumes, at the same time, the deconstruction of values and rules that sets us as ready and immutable, and the assumption of a new taste for life without any distinction of gender, ethnicity, species or class. We are talking, therefore, about art as means to remean our relations with ourselves and with the world, as a route to create new ways of thinking and living our practises, desires and values. In this perspective, in interface with the feminisms in what they have of transforming, subversive and inventive power, I used imagetic and literary resources to create other figures of subjectivity, other figurations for the body and the subject. Nomads, ciborgue and hybrid figurations are assembled as a device for us to think about multiple and post identitarian forms of subjectivization which are less tied up to essentialisms and naturalizations that justify hierarchies of power. Using a/r/tography as a method, I could hereby talk about art doing art. While exploring some of my propositions, and also various artists' propositions, I depict a track full of impressions, memories and references that were charted in order to envision the intensive maps that propelled this work. These intensities lead to the plan of molecular and micropolitic forces that are implied in the course of researching. Adopting a/r/tography to better understand these forces was the way that I found to shape some...

A partir da minha experiência como psicóloga e artista visual me propus nessa pesquisa a criar intercessores entre psicologia e arte contemporânea para pensar e produzir modos de subjetivação afeitos ao devir e às multiplicidades. Acreditando na relevância ética, estética e política de se investir na produção de subjetividades plurais e pós-identitárias, o objetivo dessa pesquisa é explorar a arte como um vetor de subjetivação capaz, potencialmente, de enriquecer e singularizar nossos campos de experiências. Positivando as diferenças enquanto alteridade, tal enriquecimento pressupõem tanto a desconstrução de valores e normas que nos são dados como prontos e imutáveis, quanto à assunção de um gosto pela vida sem distinção de raças, gêneros, classes, etnias ou espécies. Falamos, pois, da arte como meio para resignificar nossas relações com o mundo e conosco, como via para criar outros modos de pensar e viver nossas práticas, desejos e valores. Nessa perspectiva, em interface com os feminismos no que eles têm de força transformadora, subversiva e inventiva, utilizei recursos imagéticos e literários para criar outras figuras de subjetividade, outras figurações para o corpo e para o sujeito. Figurações nômades, ciborgues e híbridas convocadas para pensarmos modos de subjetivação múltiplos e pós-identitários, menos atados a essencialismos e naturalizações que justificam hierarquias de poder. Utilizando a A/r/tografia como método, pude aqui falar de arte fazendo arte. Nesse percurso, ao explorar algumas de minhas proposições, assim como a de vários outros artistas, tracei um trajeto repleto de marcas, memórias e referências que foram cartografadas para fazer ver os mapas intensivos que moveram a pesquisa. São essas intensidades que apontam para o plano das forças moleculares e micropolíticas implicadas no percurso do pesquisar. A/r/tografar essas forças...
Keywords: Arte moderna - Séc. XXI; Subjetividade; Corpo como suporte da arte; Devir (Conceito filosófico); Feminismo e arte; Feminism and art